An analysis of lexical chunks in Online Business Letters (OBL) and Business Letter Corpus (BLC): a corpus-based study / Hairul Azhar Mohamad, Muhammad Luthfi Mohaini and Pavithran Ravinthra Nath - Mohamad, Hairul Azhar; Mohaini, Muhammad Luthfi; Ravinthra Nath, Pavithran (Universiti Teknologi MARA Shah Alam, 2020)
This research investigated into the lexical density and frequencies of five types of lexical chunks located in 300 online business letters. Top 10 websites on business correspondence had been identified in terms of traffic visitors and bounce rate under one million web rankings worldwide. Criterion Sampling method was identified prior to extracting the sample letters from the websites. The data was then run with Antconc Concordance Program (ACP) for lexical density and frequency analysis. Top 15 lexical chunks in online business letters (OBL) were compared against those top 15 in Business Letter Corpus (BLC). Findings revealed that there was a total of 39 916-word tokens and 939 counts of lexical chunks found in this corpus. It was found that more lexical words do not imply more lexical chunks used in based on types of business letters. All 5 types of lexical chunks were identified and ranked in descending order; Sentence Builders (SB) as the most frequent type, followed by Collocations (COL), Deictic locutions (DLs), Polywords (POLs) and Institutionalized Expressions (IUs) as the least frequent type of lexical chunk. Sub-divisional analysis indicated that Grammatical Collocations (GCs) were more common than Lexical Collocations (LCs). Majority of lexical chunks were formed more at sentence level than phrasal level. Comparative analysis between top 15 lexical chunks in OBL and BLC discovered that most top lexical chunks in online business letters are representative of those corporate business letters in BLC. Pedagogical implications in terms of the reliability of online business letters for academic reference and future research considerations are also addressed.